2019
DOI: 10.1111/jphp.13094
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-linolenic acid ameliorates bronchial asthma features in ovalbumin-sensitized rats

Abstract: Objectives Effect of alpha-linolenic acid (ALA) against ovalbumin (OVA)induced inflammation, oxidant/antioxidant imbalance and pathological features was examined in rat. Methods Total and differential WBC count and oxidant/antioxidant levels in BALF (bronchoalveolar lavage fluid) as well as lung pathological features were investigated in five groups of rats including controls (group C), rats sensitized with OVA (group S) and S treated with either ALA (0.2 and 0.4 mg/ml) or dexamethasone. Key findings As compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…ALA, a beneficial unsaturated fatty acid, can improve lipid distribution in vivo and inhibit inflammation and antioxidative stress. 38,39 In vitro studies have shown that the level of inflammatory factors. [41][42][43] These suggest that ALA has a direct impact on the inflammatory, which is mainly achieved by inhibiting iNOS and COX-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALA, a beneficial unsaturated fatty acid, can improve lipid distribution in vivo and inhibit inflammation and antioxidative stress. 38,39 In vitro studies have shown that the level of inflammatory factors. [41][42][43] These suggest that ALA has a direct impact on the inflammatory, which is mainly achieved by inhibiting iNOS and COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…Another important pathway worth exploring is ALA metabolism, which includes ALA and 12,13‐EOTrE. ALA, a beneficial unsaturated fatty acid, can improve lipid distribution in vivo and inhibit inflammation and antioxidative stress 38,39 . In vitro studies have shown that ALA can inhibit the inflammatory characteristics of typical activated (M1) macrophages in LPS‐induced human THP‐1 cell line and reduce the production of IL‐1β, IL‐6, TNF‐α, and prostaglandin D2 40 .…”
Section: Discussionmentioning
confidence: 99%
“…α-Linolenic acid (ALA), is a short chain n-3 fatty acid which is found in flaxseed oil and has beneficial properties for human health (Boskabady, Kaveh, Shakeri, Mohammadian Roshan, & Rezaee, 2019;L. Yang et al, 2005).…”
Section: α-Linolenic Acidmentioning
confidence: 99%
“…α‐Linolenic acid (ALA), is a short chain n‐3 fatty acid which is found in flaxseed oil and has beneficial properties for human health (Boskabady, Kaveh, Shakeri, Mohammadian Roshan, & Rezaee, 2019; L. Yang et al, 2005). Antioxidant, anti‐inflammatory, anti‐obesity, and anticancer activities of ALA were shown (da Silva Marineli et al, 2014; Ren & Chung, 2007).…”
Section: Ncs That Protected Against Dox‐induced Cardiotoxicity Via Acmentioning
confidence: 99%
“…Study groups consisted of 4 groups in total: Group 1 (Control group), Group 2 (OVA), Group 3 (Asthma + Dexa 0.25 mg/kg) and Group 4 (Asthma + Tyrosol 20 mg/kg). Establishing an experimental allergic asthma model and usage doses of dexamethasone were determined according to the literature (Boskabady et al 2019). The dosage of tyrosol was made in accordance with the study of Güvenç et al (Güvenç et al 2019).…”
Section: Experimental Protocolmentioning
confidence: 99%